Medical management of congestive heart failure. - Arai, A. E. (1990)
The syndrome of congestive heart failure can result from a variety of cardiac disorders of which left ventricular dysfunction is the most common. The clinical presentation is determined by the interaction between cardiac dysfunction and a series of compensatory mechanisms that are activated throughout the body. Therapy for this disorder is best approached through an understanding of this complex relationship and an appreciation for the influence of preload, afterload, and contractility on cardiac performance. Recent important advances in therapy include the use of combined diuretic therapy, a better understanding of the value of the digitalis glycosides, and evidence that angiotensin-converting enzyme (ACE) inhibitors can relieve symptoms and prolong life. More intensive therapy earlier in the course of congestive heart failure appears to have some clinical benefit. The use of ACE inhibitors during this phase may delay progression of the underlying left ventricular dysfunction. Future therapy will be influenced by the results of ongoing trials that are testing both new agents and expanded indications for drugs that are currently available.